Threats, Victims and Unimaginable Subjects of Rights: A Genealogy of Sex Worker Governance in Poland - Dziuban, Agata (Studies in social justice, 2024)
This paper sketches the emergence of, and shifts within, the social, legal, and political figurations of sex workers in Poland. By adopting a genealogical perspective, I investigate how sex workers have been (re)constituted as subjects of governance and unimaginable social justice claimants in legislation, political debates, and law enforcement strategies. With a broad temporal scope, this article traces continuities, transformations, and disruptions within modes of sex work governance in Poland from the adoption of the first laws relating to sex work enacted during the early 19th century to the present day. Through analysis of policy documents, scholarly work on the history of sex work policies in Poland, and personal accounts by sex workers, I identify and examine two dominant discursive and legal figurations of a sex worker: as a threat, and as a victim in need of rescue and protection. While analysing the emergence of and interplay between these two figurations, this article demonstrates how these seemingly contradictory frames of recognition gradually conjoined within 20th-century Polish sex work governance strategies, rendering sex workers unimaginable subjects of rights and social justice claimants.